Multifocal pulmonary mucinous cystic neoplasm with ovarian-like stroma: Once in a blue moon-case report - Sarah Shawash; Riad Abdeljalil; Hussam Haddad (Respiratory Medicine Case Reports, 2019)
Mucinous cystic neoplasm of the lung is a rare well known entity in the WHO classification of lung tumors. It is defined as “a localized cystic mass filled with mucin and surrounded by a fibrous wall lined by well-differentiated columnar mucinous epithelium.” The presence of ovarian-like stroma is not mentioned in this definition. Reviewing the literature, we have found only one reported case mentioning this finding, described by Geramizadeh et al., in 2014. Here we present a similar case of a patient who was initially thought to have lung metastases. Hence, our case is the second one to be reported in the literature.After gross dissection of the received specimens, microscopic examination was performed. The H&E slides revealed that the lesions are composed of non-infiltrative biphasic proliferation of benign mucious epithelial cells forming cysts and gland-like structures with intervening cellular ovarian-like stroma. Differential diagnosis included hamartoma and sclerosing pneumocytoma. Additionally, ancillary studies were performed including cytokeratin AE1/AE3, EMA, TTF-1, MUC5AC, ER, CD10, SMA, CD34, S100, Inhibin, PAS, PAS/D and Mucicarmine.Immunohistochemistry showed Cytokeratin AE1/AE3, EMA and TTF-1 are positive in the epithelial cells and negative in the stromal cells. MUC5AC is weakly positive at the surface of the epithelial cells. The cells of the ovarian-like stroma are positive for ER and CD10 and focally positive for SMA. PAS, PAS/D and Mucicarmine highlighted mucin in the cystic spaces and the surface of epithelial cells. CD34, S100 and Inhibin are negative.Mucinous cystic neoplasm with ovarian-like stroma is a well-known entity in the pancreas and liver. Its occurrence in the lung has been reported in a single case in the English-written literature. We believe that it should be considered in the differential diagnosis of benign biphasic pulmonary lesions. To our knowledge, our case is the second one to be ever reported. Keywords: Pulmonary, Mucinous, Cystic, Neoplasm, Ovarian-like